Maternal age at menarche and reproductive health in young adult men: a cohort study. Issue 1 (27th October 2022) - Langergaard, Mette Jørgensen; Ernst, Andreas; Brix, Nis; Gaml-Sørensen, Anne; Tøttenborg, Sandra S; Bonde, Jens Peter E; Toft, Gunnar; Hougaard, Karin S; Ramlau-Hansen, Cecilia H
Abstract: STUDY QUESTION: Is maternal age at menarche associated with reproductive health in sons measured by semen quality, testes volume and reproductive hormone levels? SUMMARY ANSWER: Later maternal age at menarche was associated with impaired semen characteristics, lower testes volume and altered levels of reproductive hormones, while earlier maternal age at menarche was not strongly associated with reproductive outcomes in sons. WHAT IS KNOWN ALREADY: Both earlier and later maternal age at menarche may be associated with altered male reproductive health outcomes. This is the first study to investigate the potential association between maternal age at menarche and semen quality, testes volume and reproductive hormone levels in sons. STUDY DESIGN, SIZE, DURATION: In this population-based cohort study, we used data from the Fetal Programming of Semen Quality Cohort nested within the Danish National Birth Cohort. In total, 5697 sons born in 1998–2000 were invited to participate in the cohort in 2017–2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: In total, 1043 (18% of the invited) young men with information on maternal age at menarche provided a semen and blood sample, measured their testes volume, and filled in a questionnaire on health behavior and pubertal development. Maternal age at menarche was reported by the mothers during pregnancy and examined categorically (as earlier, at the same time or later than their peers), continuously and modeled as splines. We estimated relative percentage differences in the reproductive outcomes using negative binomial regression models. Further, we did a mediation analysis to investigate the potential mediating role of timing of the sons' pubertal development. MAIN RESULTS AND THE ROLE OF CHANCE: Sons whose mothers had age at menarche later than peers had 15% lower (95% CI: −27%; 0%) sperm concentration, 14% lower (95% CI: −28%; 1%) total sperm count, 7% higher (95% CI: 0%; 14%) proportion of nonprogressive or immotile spermatozoa, 6% lower (95% CI: −11%; 0%) testes volume, 6% lower (95% CI: −12%; 1%) luteinizing hormone, 6% lower (95% CI: −12%; 1%) sex hormone-binding globulin and 5% lower (95% CI: −9%; 0%) testosterone levels compared with sons whose mothers had age at menarche at the same time as peers. Our study did not suggest that earlier maternal age at menarche was strongly associated with semen quality, testes volume or reproductive hormones in sons. However, the spline analyses indicated a potential inverted U-shaped association for sperm concentration and testes volume, and levels of sex hormone-binding globulin and testosterone. We found no strong evidence of mediation by timing of the sons' own pubertal development. LIMITATIONS, REASONS FOR CAUTION: There was a rather low participation rate in the Fetal Programming of Semen Quality Cohort and we tried to counter it by applying selection weights. Maternal age at menarche was recalled during pregnancy, which may introduce misclassification, most likely nondifferential. Inaccuracy of the sons' recalled pubertal development years after the event may result in underestimation of the possible mediating role of pubertal timing. WIDER IMPLICATIONS OF THE FINDINGS: Our findings may represent a degree of shared heritability of reproductive health or be a result of an underlying epigenetic profile or unknown shared environmental, cultural or dietary exposure, causing both altered age at menarche and impaired reproductive health outcomes in sons. However, the exact mechanism for the investigated association remains unknown. STUDY FUNDING/COMPETING INTEREST(S): This article is part of the ReproUnion collaborative study, cofinanced by the European Union, Intereg V ÖKS (20200407). The FEPOS project was further funded by the Lundbeck Foundation (R170-2014-855), the Capital Region of Denmark, Medical doctor Sofus Carl Emil Friis and spouse Olga Doris Friis's Grant, Axel Muusfeldt's Foundation (2016-491), A.P. Møller Foundation (16-37), the Health Foundation and Dagmar Marshall's Fond. Additionally, this study received funding from Aarhus University. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.